Numeric simulation study of a textile processing plant for residual energy recovery - Peraldo Ramos, Anita Etelvina (2022)
Currently, textile processing plants need to control the conditions associated with the spinning process, being the air conditioning of working environments an important factor in the quality and productivity of these processes. The benefits obtained from the optimization of this air conditioning help to guide a lower energy consumption, helping to improve the positioning of the products and providing profitability in the operation processes. Due to the advantages obtained in the air conditioning process, this work proposes a system that allows reusing the residual energy generated at the outlet of the ventilation ducts. This residual energy is fed into the plant to reduce the high temperatures observed in the ceiling. Consequently, this approach will generate a decrease in the service demand of the air conditioning system and reduce operating costs. Also, to verify this proposal, a multiphysics numerical simulation is performed and compared to a conventional air conditioning system. The simulation incorporates turbulence models to represent the flow in the ventilation ducts. In addition, this simulation considers the heat transfer that is generated by the equipment operating in this textile plant. The results of the multiphysics simulation show the temperature fields, flow lines, among other important data obtained from the numerical simulation. All the results are given for a section of the environment of these plants and verify the efficiency of the proposal of this work.